Employee-friendly practices and corporate financial performance: Evidence from a frontier market - Nguyễn, Đức Nguyên (Taylor & Francis, 2022)
This study investigates the association between employee-friendly schemes and firm financial performance using a frontier market, Vietnam, as a research context. We employ Anphabe’s “Top 100 Vietnam Best Places to Work” lists to identify companies with ideal employee-friendly practices. Using a data sample of more than 3,800 firm-year observations, we document a strong and positive relationship between employee welfare and firm performance measured by Tobin’s q. Our result is robust to a battery of sensitivity tests, including an alternative indicator of financial performance, alternative selection criteria, and different econometric techniques.